Modeling of litho-hydrological conditions as an element of impact assessment on the environment: the context of ecological safety - Шаравара, В. В.; Гулевець, Д. В.; Мовчан, Я. І. (Problems of Environmental Biotechnology, 2015)
The publication highlights the impact of particular geological structure of the formation of ecological situation in the regions of lithospheric environment accommodation starting positions of ballistic missiles. Designated role of forming a model of litho-hydrological conditions of the study area in the implementation of environmental impact assessment.